SISTEM PENUNJANG KEPUTUSAN KELULUSAN SISWA PADA SMK LAKSAMANA MARTADINATA DENGAN MENERAPKAN BAHASA PEMROGRAMAN JAVA - Ahir Yugo Nugroho Harahap (JSIK (Jurnal Sistem Informasi Kaputama), 2020)
Decision Support Systems (SPK) are designed to support all stages of decision making starting from identifying problems, selecting relevant data, determining the approach used in the decision making process, to evaluating alternative choice